Tentativas, riesgos y resultados - López Warriner, Santiago (2009)
The prevailing view among Criminal Law scholars is that hypothetical causal courses should not be acknowledged any significance at all. This article is aimed at presenting some statements against such view, so as to make some remarks concerning the principle of attribution developed by Marcelo Sancinetti to solve such cases, called ?principle of subrogation?. It is stated that the line of reasoning developed in that respect by Sancinetti implies considering the negative result as decisive, which appears to be in contradiction to the central idea of the author. Finally, a solution to the problem in question is suggested, in accordance with a subjective theory of Criminal Law and on the basis of a reckless indirect liability